Work-family balance, gender and policy - Lewis, Jane (Cheltenham, UK : Edward Elgar, 2009)
Looks at the three main components of work-family policy packages - childcare services, flexible working patterns and entitlements to leave from work in order to care - across EU15 Member States, with comparative reference to the US. This work also provides an examination of developments in the UK
1. Introduction -- 2. The policymaking context : behaviour and attitudes -- 3. Work-family balance policies : comparisons and issues -- 4. Patterns of development in work-family balance policies for parents in France, Germany, the Netherlands and the UK during the 2000s -- 5. Policy development in the UK, 1997-2007 -- 6. Concluding reflections on gender equality and work-family balance policies
Includes bibliographical references and index
Keywords: Labor policy -- European Union countries; Work and family -- European Union countries